Trigonella coerulescens subsp. ayvalikensis (Fabaceae), a new taxon from Balιkesir, western Anatolia - Erdoğan, Eyüp; Selvi̇ Selami̇; Tümen, Gülendam (Phytotaxa, 2017)
Trigonella coerulescens subsp. ayvalikensis (Fabaceae) is described and illustrated from western Anatolia, Turkey. It grows on sandy soil and flowers from March to May in coastal areas. Diagnostic characters are given and the taxon compared to the other two subspecies; Trigonella coerulescens subsp. coerulescens and Trigonella coerulescens subsp. kemerensis.